Asymptotic expansion for the density function of the series scheme of a random variables in the large deviation in Cramer zone - Deltuvienė, Dovilė; Saulis, Leonas (Lietuvos matematikos rinkinys, 2001)
In this work, the expansion of the density function of series schemes of independent variables ξ(n)1,ξ(n)2 ,..., ξ(n)j,   with means Eξ(n)j = 0, and dispersions σ(n)2j = Eξ(n)2j   has been obtained in the Cramer zone of large deviations. The result was obtained, based on General Lemma 6.1 [2] by joining the methods of characteristic functions and cumulants. The work broadens theory of sums of random variables [1] and in special case improves S.A. Book [5] results of sums of random variables with weights.